2004
DOI: 10.1271/bbb.68.501
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Cut Lettuce Treated by Heat Shock: Prevention of Enzymatic Browning, Repression of Phenylalanine Ammonia-lyase Activity, and Improvement on Sensory Evaluation during Storage

Abstract: Stored cut lettuce gradually turns brown on the cut section after several days of storage, because cutting induces phenylalanine ammonia-lyase (PAL) activity, the biosynthesis of polyphenol is promoted, and the polyphenols are oxidized by polyphenol oxidase. Here, the effect of heat shock treatment at 50 C for 90 s on the quality of cut lettuce during cold storage was examined. The heat shock treatment significantly repressed the induction of PAL activity and phenolics accumulation in cut lettuce during storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 23 publications
3
46
3
4
Order By: Relevance
“…The combination of GT and heat-shock kept lower potential browning values than GT treatment at room temperature (Part II, Fig. 6B) thos e results are in agreement with findings from Murata, Tanaka, Minoura and Homma (2004) and Saltveit (2001). Samples treated with chlorine showed higher levels of potential browning than samples treated with Browning in photosynthetic and vascular tissues, general levels of browning and fresh appearance of the samples were evaluated b the y sensory panel.…”
Section: Potential Browningsupporting
confidence: 84%
“…The combination of GT and heat-shock kept lower potential browning values than GT treatment at room temperature (Part II, Fig. 6B) thos e results are in agreement with findings from Murata, Tanaka, Minoura and Homma (2004) and Saltveit (2001). Samples treated with chlorine showed higher levels of potential browning than samples treated with Browning in photosynthetic and vascular tissues, general levels of browning and fresh appearance of the samples were evaluated b the y sensory panel.…”
Section: Potential Browningsupporting
confidence: 84%
“…5B). This profile of mung bean sprouts is almost the same as that of cut lettuce (Murata et al, 2004). It is supposed that phenolics formed in mung bean sprouts during cold storage are oxidized by the action of PPO and therefore browning is apparent.…”
Section: Methodsmentioning
confidence: 64%
“…The gradual browning of cut lettuce during cold storage can be repressed by heat-shock treatment, resulting in better quality (Loaiza-Velarde et al, 1997;Murata et al, 2004). Heat-shock treatment can also repress the decay, softening, and color change of strawberries during storage (Civello et al, 1997) and maintain the green color of broccoli (Funamoto et al, 2002;Funamoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the combination of chlorine disinfectant and mild heat not only enhanced the bactericidal effect, but also improved the quality of vegetables. For example, Murata et al (2004) reported that the organoleptic quality of cut lettuce subjected to heat shock was significantly better than that of the untreated control. Also, Roura et al (2008) reported that heat shock in a 50℃ water-bath for 2 min prevented browning of fresh-cut lettuce by reducing phenylalanine ammonia lyase activity.…”
Section: Efficacy Of Combining Chlorine Disinfectants With Physicalmentioning
confidence: 99%